2019
DOI: 10.1111/jocd.13197
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of photodynamic therapy for the treatment of inflammatory acne vulgaris: A systematic review and meta‐analysis

Abstract: Acne vulgaris is a kind of chronic inflammatory dermal disorder that occurs in the sebaceous glands and hair follicles on face, neck, back, and chest, which has affected almost every adult and adolescent during their lifetime at a certain time. 1,2 Studies have shown that the incidence of acne is as high as 85%, which has greatly affected the psychology and quality of life of patients even though it is not life-threatening. 3 The clinical features of acne include seborrhea, noninflammatory lesion (including cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…This assumption was confirmed in our current study, where DL-PDT was shown to be as effective as C-PDT. These results are in line with a recent meta-analysis and systemic review of trials using PDT for acne 23 that concluded that a specific wavelength within the visible light spectrum made little difference to PDT efficacy.…”
Section: F I G U R Esupporting
confidence: 89%
See 1 more Smart Citation
“…This assumption was confirmed in our current study, where DL-PDT was shown to be as effective as C-PDT. These results are in line with a recent meta-analysis and systemic review of trials using PDT for acne 23 that concluded that a specific wavelength within the visible light spectrum made little difference to PDT efficacy.…”
Section: F I G U R Esupporting
confidence: 89%
“…While some groups reported that C-PDT was an effective treatment for both open and closed comedones, 22,24 several others reported not having shown that effect. 4,19,20,23,25 When asked to elaborate, they stated that their response was influenced by the study protocol, which included both treatments for all of the patients, therefore making it difficult to arrive at a clear-cut decision.…”
Section: F I G U R Ementioning
confidence: 99%
“…Its efficacy in the treatment of acne has been shown by several studies. 28,29 A two-center, prospective assessor-blinded, proof-of-concept study assessed the effectiveness of PDT with red light in combination with 5% gel aminolevulinic acid in the treatment of the inflammatory component of mild-to-moderate acne. 30 Thirty-five patients with moderate acne were enrolled and clinical status was assessed considering Global Acne Grade System (GAG) at baseline and after three sessions of PDT (each of 15 minutes) with a statistically significant reduction of GAG score (P = .0001).…”
Section: Phototherapymentioning
confidence: 99%
“…Again, in the context of phototherapies, the option of photodynamic therapy (PDT) should be mentioned. Its efficacy in the treatment of acne has been shown by several studies 28,29 . A two‐center, prospective assessor‐blinded, proof‐of‐concept study assessed the effectiveness of PDT with red light in combination with 5% gel aminolevulinic acid in the treatment of the inflammatory component of mild‐to‐moderate acne 30 .…”
Section: Treatment Of Mild‐to‐moderate Acnementioning
confidence: 99%
“…Photodynamic therapy (PDT) has been recognized as a favorable alternative treatment for mild to severe acne, especially for lesions insensitive to topical therapy and oral antibacterials, or those inapplicable for isotretinoin 10 . Nonetheless, the obvious adverse events (like severe pain, burning sensation, erythema, and edema 11 ) and the high cost may greatly restrict the further application of PDT. Intense pulse light (IPL) has been applied for more than 20 years 9 .…”
Section: Introductionmentioning
confidence: 99%